Estratégias fotocatalíticas para a síntese de miméticos de glicopeptídeos e síntese do fármaco anticâncer Carfilzomibe - Chavarro Vélez, Jeimy Alejandra (Universidade Federal de São Carlos, 2026)
Peptide-based structures play a crucial role in biological recognition and contemporary drug development because of their structural versatility and functional significance. In this context, this thesis reports the development of photocatalytic methodologies for the synthesis of glycopeptide mimetics and sustainable synthetic routes for the peptide-based anticancer drug Carfilzomib. The work is divided into two chapters addressing methodological and applied challenges in peptide chemistry and pharmaceutical synthesis. In Chapter 1, visible-light-mediated photocatalytic strategies were developed for the diastereoselective synthesis of glycopeptide analogues. Although C-glycosides provide enhanced chemical and enzymatic stability, their synthesis typically requires complex multistep protocols and presents significant challenges in stereochemical control. To address these limitations, a photocatalytic radical addition strategy was investigated using glycosyl nitrones and 4-amido-1,4-dihydropyridines derived from amino acids and peptides. This approach enables stereoselective carbon–carbon bond formation under mild conditions, providing a robust platform for the construction of neoglycosylated peptide frameworks. Chapter 2 focuses on the development of an efficient and scalable synthetic route to Carfilzomib; a second-generation proteasome inhibitor used in the treatment of multiple myeloma. Considering the limited production of high-cost pharmaceuticals, this study proposes a sustainable and accessible synthetic strategy for this clinically relevant drug. The approach involves the visible-light photocatalytic synthesis of the unnatural amino acid L-homophenylalanine, followed by solid-phase peptide synthesis to assemble the peptide backbone and coupling of an epoxide fragment. An alternative route using a proline-functionalized resin enables controlled peptide elongation and cleavage via a Grignard reaction to generate a terminal alkene, followed by asymmetric epoxidation of α,β-unsaturated ketones as a late-stage functionalization step. According to the results obtained, photocatalysis and modern synthetic methodologies offer robust, stereocontrolled, and sustainable solutions for the synthesis of glycopeptide mimetics and complex peptide-based pharmaceuticals. Overall, this thesis demonstrates the applicability of visible-light-driven processes and strategic molecular design in addressing key challenges in glycopeptide chemistry and pharmaceutical manufacturing, contributing to advances in contemporary drug discovery and production.
Photocatalytic strategies for the synthesis of glycopeptide mimetics and synthesis of the anticancer drug Carfilzomib
Keywords: Fotocatálise; Glicopeptídeos; C-glicosilação; Química radicalar; Derivados de aminoácidos; Síntese de peptídeos; Síntese peptídica em fase sólida (SPPS); Química em fluxo contínuo; Aminoácidos não naturais; Carfilzomibe; Mieloma múltiplo; Síntese sustentável; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::FOTOQUIMICA ORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA; 9. Indústria, Inovação e Infraestrutura